2021
DOI: 10.1002/hed.26830
|View full text |Cite
|
Sign up to set email alerts
|

Current salivary biomarkers for detection of human papilloma virus‐induced oropharyngeal squamous cell carcinoma

Abstract: Human papilloma virus (HPV) infection is a key risk factor and etiology for oropharyngeal squamous cell carcinoma (OPSCC). HPV‐induced OPSCC is rapidly increasing in incidence, with men experiencing increased mortality. When identified at an early stage, HPV‐induced OPSCC can be successfully treated. Diagnosis of HPV‐related OPSCC relies on an expert physical examination and invasive biopsy. Since saliva bathes the oropharyngeal mucosa and can be collected noninvasively, saliva obtained via salivary risings is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 101 publications
(203 reference statements)
0
2
0
Order By: Relevance
“…59 In a study led by Rooper et al 59 100% and specificities from 88% to 100%. 55 There are still some limitations regarding ISH. The current understanding of interpreting ISH signals lacks uniform agreement on established thresholds, which adds complexity to their interpretation compared to the more straightforward p16 IHC.…”
Section: Ish For Hpv Detectionmentioning
confidence: 99%
See 1 more Smart Citation
“…59 In a study led by Rooper et al 59 100% and specificities from 88% to 100%. 55 There are still some limitations regarding ISH. The current understanding of interpreting ISH signals lacks uniform agreement on established thresholds, which adds complexity to their interpretation compared to the more straightforward p16 IHC.…”
Section: Ish For Hpv Detectionmentioning
confidence: 99%
“…Of note, RISH signals were visualized at low to medium magnification in 97% of positive cases. Over the last decade, studies on RISH have shown excellent diagnostic performance, with sensitivities ranging from 87% to 100% and specificities from 88% to 100% 55 …”
Section: Human Papillomavirus (Hpv)‐driven Head and Neck Cancers (Hncs)mentioning
confidence: 99%
“…Saliva testing has demonstrated its applicability in different settings, for example, for detection of oral cancer such as squamous cell carcinoma [4], identification of infectious diseases (helicobacter pylori [5], hepatitis [6], papilloma virus [7], etc. ), hormone monitoring [8][9][10], and screening for chronic kidney disorders [11].…”
Section: Of 15mentioning
confidence: 99%
“…Not only are biofluids a rich source of molecular proteins and peptides, but their collection is also relatively simple and minimally invasive. For instance, salivary biomarkers have been proposed to detect and monitor inflammatory and infectious diseases including chronic inflammatory disorders (e.g., inflammatory bowel and periodontal conditions) and sexually transmitted infections (e.g., HIV and HPV) ( 4 7 ). The diagnostic accuracy of molecular biomarkers, however, need to be rigorously established before they transition to the convenience of POC testing.…”
Section: Introductionmentioning
confidence: 99%